Mode of Inheritance and Interrelationship among Age at First Egg, Body Weight at First Egg and Weight of First Egg in Local by Exotic Inbred Chicken Crosses - Udeh, I. (International Journal of Poultry Science, 2010)
The interrelationship among Age at First Egg (AFE), Body Weight at First Egg (BWFE) and Weight of First Egg (WFE) and their inheritance were studied in the F1 crossbred groups generated from the mating of inbredlines of two exotic and the local chickens. The birds were reared on deep litter pens from day old to 24 weeks of age when all the groups had started laying. The results indicated that the F1 crossbred groups differed significantly (p